Measurement of the longitudinal spin asymmetries for weak boson production in proton-proton collisions at √s=510 GeV - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert (Physical review, 2019)
We report new STAR measurements of the single-spin asymmetries AL for W+ and W− bosons produced in polarized proton-proton collisions at √s=510 GeV as a function of the decay-positron and decay-electron pseudorapidity. The data were obtained in 2013 and correspond to an integrated luminosity of 250 pb−1. The results are combined with previous results obtained with 86 pb−1. A comparison with theoretical expectations based on polarized lepton-nucleon deep-inelastic scattering and prior polarized proton-proton data suggests a difference between the ¯u and ¯d quark helicity distributions for 0.05<x<0.25. In addition, we report new results for the double-spin asymmetries ALL for W±, as well as AL for Z/γ∗ production and subsequent decay into electron-positron pairs.